1996
DOI: 10.1108/02651339610131414
|View full text |Cite
|
Sign up to set email alerts
|

Logistics strategy: does it travel well?

Abstract: Logistics has emerged as a subject of considerable interest in the wake of American transport deregulation, European unification efforts, global supply chain management concepts, and growth in regional trading blocs. Traditionally viewed as a cost centre it is now fashionable to speak of logistics in a strategic context -an element of possible advantage in an increasingly competitive international trading environment. Embedded in this view of logistics is the idea of logistics strategy.To date, work in this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
9
0
2
Order By: Relevance
“…Previous research (Autry, Zach, and Lamb 2008;Clinton and Closs 1997;Kohn and McGinnis 1997a;Kohn and McGinnis 1997b;McGinnis and Kohn 2002) has established that independent variables, such as Process Strategy, Market Strategy, and Information Strategy, vary within organizations. However, the effect of logistics strategy independent variables on outcomes, such as Logistics Coordination Effectiveness, Customer Service Commitment, and Company/Division Competitiveness, has not been as closely examined.…”
Section: Comp-2mentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research (Autry, Zach, and Lamb 2008;Clinton and Closs 1997;Kohn and McGinnis 1997a;Kohn and McGinnis 1997b;McGinnis and Kohn 2002) has established that independent variables, such as Process Strategy, Market Strategy, and Information Strategy, vary within organizations. However, the effect of logistics strategy independent variables on outcomes, such as Logistics Coordination Effectiveness, Customer Service Commitment, and Company/Division Competitiveness, has not been as closely examined.…”
Section: Comp-2mentioning
confidence: 97%
“…Subsequent research has concluded that the Bowersox and Daugherty (1987) typology was worthy of further research (McGinnis and Kohn 1993); that the typology is "promising" (Clinton and Closs 1997); that multiple strategies are present in all organizations to varying degrees (Kohn and McGinnis 1997a); that process strategy explains more variance in logistics coordination effectiveness than does market and information strategies; and that the typology can be used for examining logistics strategy in U.S. manufacturing firms (McGinnis and Kohn 2002).…”
Section: Literature Review and Development Of Research Hypothesesmentioning
confidence: 98%
“…Instead, it is vital to make necessary adjustments and pretests, despite the common language base. Clinton and Calantone (1996) found conceptual problems between English-speaking countries. Equally, it is important to note that cross-cultural research issues are not limited to research in different countries but can arise in research within the same country.…”
Section: Conceptual Equivalencementioning
confidence: 98%
“…A logisztikai képességek erôforrás-alapú értelmezése és vizsgálata a nemzetközi irodalomban is megtalálható (Fewcett és társai, 1997; Morash -Clinton, 1997;Clinton -Closs, 1997;Olavarrieta -Ellinger, 1997; Lynch és társai, 2000; Shang -Marlow, 2004 ni, hogy az elemzés soron használt változók mindegyikét 1-5 Likert-skálán mértük, elemzéseinket pedig az SPSS Statistics 18. programcsomag segítségével végeztük el.…”
Section: A Logisztikai Képességek éRtelmezése éS Méréseunclassified